Perempuan Pekerja dalam Perspektif Hukum Keluarga Islam - Husniati, Husniati; Rahmawati, Rahmawati; Nur, Muhammad Tahmid Nur (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This thesis discusses the views of husbands and wives on family responsibilities, analyzes the factors that lead women to work, and analyzes the perspectives of Islamic family law on working women. This research employs a library research method, employing a normative approach, linking the issues encountered to Islamic legal norms. The primary sources in this research are journals, books, and articles. The literature was compiled by searching for reading materials relevant to the issues discussed, namely working women. The results of this study indicate that women who make the decision to work do so to help ease their husband's burden in providing for their family. They also fulfill their right to develop a career in a specific field. The researcher's research reveals that, with the development of the times and changes in lifestyle, many women are participating in the public sector to contribute to the economy or simply to advance their careers. There are several reasons for women to become working women, namely because of the main factors of economics, self-existence, education, social, culture, as well as the interests and talents they have, when viewed from Islamic family law there are no verses that prohibit women from working and from this research, working women when viewed from the perspective of Islamic family law do not conflict with Islamic law if carried out by women with conditions that do not deviate from Islamic law and with the permission of their husband or family.